Sex differences in elite ski mountaineering aerobic performance - Schorderet, Forrest; Mottet, Justin; Lathion, Aurélien; Raberin, Antoine; Bourdillon, Nicolas; Millet, Grégoire P. (Frontiers in Sports and Active Living, 2025)
Ski mountaineering (SkiMo) sprints will debut as an Olympic sport in 2026, yet research on the discipline remains scarce compared to other winter sports. The demanding sprint format, with most of the race time spent on uphill sections, highlights the importance of body composition and maximal oxygen consumption (V˙O2max). While previous studies have primarily focused on male athletes, this study aimed to analyze sex differences in physiological parameters of elite SkiMo athletes, hypothesizing that differences in vertical velocities (vV) would surpass those in V˙O2 at ventilatory thresholds (VT1, VT2) and maximal intensity (MAX), respectively. Twenty elite/worldclass Swiss SkiMo athletes (6 women, 14 men, aged 20–32 years) participated in the study. They performed a graded exercise test to exhaustion on a treadmill set at a 25% slope, with breath-by-breath gas exchanges. Elite female SkiMo athletes had a V˙O2 value 13.6% lower at MAX (64.0 ± 3.8 vs. 72.8 ± 5.5 ml/kg/min; p = 0.002) and 15.5% lower at VT2 (54.8 ± 2.8 vs. 62.2 ± 5.8 ml/kg/min; p = 0.009) than their male counterparts. Interestingly, the sex-differences in vV at both MAX (1,825 ± 113 vs. 2,125 ± 156 m/h; p < 0.001; 16.4%) and VT2 (1,412 ± 56 vs. 1,696 ± 151 m/h; p < 0.001; 20.1%) intensities were consistently larger than the differences in V˙O2. Moreover, fat mass was higher in females (15.2 ± 1.0 vs. 6.6 ± 0.6%; p = 0.004). Additionally, vertical running energy cost at VT2 was significantly higher in females compared to males (2,329 ± 95 vs. 2,199 ± 60 ml/kg/kmv; p = 0.018). Sex differences in uphill velocities (16.4–20.1%) exceeded those in V˙O2 (13.6–16.5%). Investigation on the underlying mechanisms is required but several factors may contribute to this pronounced sex difference in uphill velocity beyond aerobic power alone. Overall, the present findings align with recent studies reporting a 16%–20% difference in performance times when investigating sex differences in uphill displacement. The performance gap between men and women appears to be larger in uphill sports.